1997
DOI: 10.1083/jcb.136.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Lies Downstream of Parathyroid Hormone–related Peptide in a Signaling Pathway That Regulates Chondrocyte Maturation during Skeletal Development

Abstract: Parathyroid hormone–related peptide (PTHrP) appears to play a major role in skeletal development. Targeted disruption of the PTHrP gene in mice causes skeletal dysplasia with accelerated chondrocyte maturation (Amizuka, N., H. Warshawsky, J.E. Henderson, D. Goltzman, and A.C. Karaplis. 1994. J. Cell Biol. 126:1611–1623; Karaplis, A.C., A. Luz, J. Glowacki, R.T. Bronson, V.L.J. Tybulewicz, H.M. Kronenberg, and R.C. Mulligan. 1994. Genes Dev. 8: 277–289). A constitutively active mutant PTH/PTHrP receptor has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
218
4
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(242 citation statements)
references
References 46 publications
18
218
4
2
Order By: Relevance
“…4B), which is partly explained by the expansion of the hypertrophic layer of chondrocytes. Amling et al (14) found that Bcl2 expression is increased in late proliferative and prehypertrophic chondrocytes in transgenic mice overexpressing PTHrP in chondrocytes, but we found no change in Bcl2 mRNA levels in the growth plates of Coll2-CreER T :PPR fl/fl mice after administration of Tam. We focused on the BH3-only protein Bad because Bad is regulated by PKA, and therefore is a candidate regulator of apoptosis downstream of activation of the PPR.…”
Section: Discussioncontrasting
confidence: 44%
“…4B), which is partly explained by the expansion of the hypertrophic layer of chondrocytes. Amling et al (14) found that Bcl2 expression is increased in late proliferative and prehypertrophic chondrocytes in transgenic mice overexpressing PTHrP in chondrocytes, but we found no change in Bcl2 mRNA levels in the growth plates of Coll2-CreER T :PPR fl/fl mice after administration of Tam. We focused on the BH3-only protein Bad because Bad is regulated by PKA, and therefore is a candidate regulator of apoptosis downstream of activation of the PPR.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous transgenic experiments have shown that Bcl-2 is a component of the PTH signaling pathway (11). We show here that the Bcl-2 level is regulated by the p38 MAPK activity.…”
Section: P38 Mapk Mediates Pth-regulated Chondrocyte Differentiationmentioning
confidence: 48%
“…elevating intracellular cAMP, thereby activating cAMP-dependent protein kinase A (PKA) or activating phospholipase C that results in an increase in intracellular free calcium and activation of protein kinase C (PKC) (10). It has also been shown that Bcl-2, an anti-apoptosis molecule, is also involved in the PTH/PTHrP signaling pathway in chondrocytes (11). In this study, we will determine the involvement of PKA and PKC pathways in transducing PTH/ PTHrP signals to regulate chondrocyte differentiation.…”
mentioning
confidence: 99%
“…These results suggested that Sox9 controls chondrocyte differentiation via PTHrP. PTHrP is known to play an important role in the regulation of proliferation, maturation, and apoptosis processes in chondrocytes (Weir et al, 1996;Amling et al, 1997;Zerega et al, 1999;Beier et al, 2001;Yamanaka et al, 2003). Furthermore, previous genetic studies have suggested an inhibitory role for Sox9 in the maturation of chondrocytes (Akiyama et al, 2004).…”
Section: Sox9 Family Induces Pthrp Expression In Chondrocytesmentioning
confidence: 67%